Studies of variability in Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) through acorn protein profile analysis. (Journal of proteomics, 2011)
Studies of variability in Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.), the dominant tree species in the typical Mediterranean forest, have been carried out by using electrophoresis-based proteomic analysis of acorns. Ten populations distributed throughout the Andalusia region have been surveyed. Acorns were sampled from individual trees and proteins extracted from seed flour by using the TCA-acetone precipitation protocol. Extracts were subjected to SDS-PAGE and 2-DE for protein separation, gel images captured, spot or bands quantified, and subjected to statistical analysis (ANOVA, SOM and clustering). Variable bands or spots among populations were subjected to MALDI-TOF/TOF and LC-MS/MS for identification. The protein yield of the used protocol varied among populations, and it was in the 2.92-5.92 mg/g dry weight range. A total of 23 bands were resolved by SDS-PAGE in the 3-35 kDa Mr range, with 8 and 12, out of the total, showing respectively qualitative and quantitative statistically significant differences among populations. Data allowed grouping populations, with groups being correlated according to geographical location and climate conditions, to northern and southern, as well as the discrimination of both mesic and xeric groups. Acorn flour extracts from the most distant populations were analyzed by 2-DE, and 56 differential spots were proposed as markers of variability. Identified proteins were classified into two principal categories; storage and stress/defense protein. Besides providing the first reference map of mature acorn seeds, the use of SDS-PAGE and proteomics in characterizing natural biodiversity in forest trees will be discussed.